Design, Sustainable Synthesis and Biological Evaluation of a Novel Dual α2A/5-HT7 Receptor Antagonist with Antidepressant-Like Properties - Vittorio Canale; Magdalena Kotańska; Anna Dziubina; Matylda Stefaniak; Agata Siwek; Gabriela Starowicz; Krzysztof Marciniec; Patryk Kasza; Grzegorz Satała; Beata Duszyńska; Xavier Bantreil; Frédéric Lamaty; et al. (Molecules, 2021)
The complex pathophysiology of depression, together with the limits of currently available antidepressants, has resulted in the continuous quest for alternative therapeutic strategies. Numerous findings suggest that pharmacological blockade of α2-adrenoceptor might be beneficial for the treatment of depressive symptoms by increasing both norepinephrine and serotonin levels in certain brain areas. Moreover, the antidepressant properties of 5-HT7 receptor antagonists have been widely demonstrated in a large set of animal models. Considering the potential therapeutic advantages in targeting both α2-adrenoceptors and 5-HT7 receptors, we designed a small series of arylsulfonamide derivatives of (dihydrobenzofuranoxy)ethyl piperidines as dually active ligands. Following green chemistry principles, the designed compounds were synthesized entirely using a sustainable mechanochemical approach. The identified compound 8 behaved as a potent α2A/5-HT7 receptor antagonist and displayed moderate-to-high selectivity over α1-adrenoceptor subtypes and selected serotonin and dopaminergic receptors. Finally, compound 8 improved performance of mice in the forced swim test, displaying similar potency to the reference drug mirtazapine.